Aplikasi Pupuk Organik Cair Berbasis Urine Kelinci sebagai Upaya untuk Meningkatkan Kualitas Tanah Pertanian di Desa Tangsil Wetan, Wonosari, Bondowoso: Application of Liquid Organic Fertilizer Based on Rabbit Urine to Increase the Quality of Agricultural Soil in Tangsil Wetan Village, Wonosari, Bondowoso - Tamami, Akfani Jahval; Rayhan, Nevanda Shaquille; Syahrulita, Dita Crisma; Nabila, Cinta Rivani; Jamala, Tipta; Fitriyah, Azhaara Raihanah 'Urfatul; Hanafi, Mustika Intan Sahifah; Vania, Amanda; Farhan, Muhammad; Azhar, Adella Rahani; Ningsih, Fitriyah; Muflihah, Yeni Maulidah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The low nutrient content and acidic soil pH (pH 5) are a significant problem in Tangsil Wetan Village, Bondowoso, where most of the population works as farmers. This condition affects the growth and productivity of the farm's produce. To address this issue, we introduced liquid organic fertilizer derived from rabbit urine. The work was implemented in several phases: socialization, training in the production of rabbit urine-based liquid organic fertilizer, fertilizer application, and subsequent observation. The fertilizer production process involves fermenting rabbit urine mixed with molasses, EM4 liquid, and water for ten days. The resulting liquid fertilizer is then applied to the rice fields in three stages of spraying. We conducted observations to measure soil parameters, such as pH, before and after fertilizer application. The results indicated an improvement in soil conditions after the three sprayings, with a notable increase in soil pH from 5.0 to 5.4. However, the short-term impact on plants has been limited; consistent application is necessary to achieve maximum results.